Solve (D2+2DD'+D'2)z=cos(x+2y)+ex-2y.
Given, "(D^2 + 2DD'+D'^2)z = \\cos(x+2y) + e^{x - 2y}"
The auxiliary equation is "m^2 + 2m +1 =0". The roots of the auxiliary equation are "m = -1~(\\text{twice})". The complementary function is "C.F = f_1(y-x) + xf_2(y-x)."
The particular integral is
"\\begin{aligned}\nP.I &= \\dfrac{1}{D^2 + 2DD'+D'^2} \\cos(x + 2y) + \\dfrac{1}{D^2 + 2DD'+D'^2} e^{x - 2y}\\\\\n&~~~~~~\\text{Replacing $D^2 = -1, DD' =-2, D'^2 = -2^2$ for the first term and }\\\\\n&~~~~~~\\text{Replacing $D = 1, D' = -2$ for the second term, we get}\\\\\n\n&= \\dfrac{1}{-1^2+2*(-2)-2^2}\\cos(x+2y) + \\dfrac{1}{1+2*1*-2+(-2)^2}e^{x-2y}\\\\\n&=\\dfrac{-\\cos(x+2y)}{9}+e^{x-2y}\n\\end{aligned}"
Hence the solution is "z = \\text{C.F + P.I} = f_{1}(y-x)+xf_{2}(y-x)+e^{x-2y}-\\dfrac{\\cos(x+2y)}{9}"
Comments
Leave a comment